Pengaruh Literasi Keuangan Syariah dan Kemudahan Terhadap Penggunaan Mobile Banking Syariah di Masyarakat Desa Bapangan Kecamatan Jepara - Rita Dwi Octavia; Wahidullah Wahidullah; Ahmad Fauzan Mubarok (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze the influence of Islamic financial literacy and ease of use on the adoption of Islamic mobile banking in the community of Bapangan Village, Jepara District. The background for this research is the relatively low adoption rate of Islamic mobile banking despite its significant potential, which is presumed to be influenced by understanding (literacy) and technological ease of use. This research employed a quantitative approach. The research sample consisted of 98 respondents who are customers of Islamic banks in Bapangan Village, selected using a purposive sampling technique. Data was collected via questionnaires and analyzed using multiple linear regression. The results showed that: (1) Islamic financial literacy has a positive and significant effect on the adoption of Islamic mobile banking (Sig. 0.000); (2) Ease of use has a positive and significant effect on the adoption of Islamic mobile banking (Sig. 0.000); and (3) Islamic financial literacy and ease of use simultaneously have a positive and significant effect on the adoption of Islamic mobile banking (Sig. 0.000). The Adjusted R Square value of 0.894 indicates that 89.4% of the variation in Islamic mobile banking adoption can be explained by these two variables. These findings imply that enhancing literacy and optimizing application usability are key factors in driving the adoption of Islamic digital banking services.